2011
DOI: 10.1016/s1078-5884(11)60014-2
|View full text |Cite
|
Sign up to set email alerts
|

Chapter IV: Treatment of Critical Limb Ischaemia

Abstract: Recommendations stated in the TASC II guidelines for the treatment of peripheral arterial disease (PAD) regard a heterogeneous group of patients ranging from claudicants to critical limb ischaemia (CLI) patients. However, specific considerations apply to CLI patients. An important problem regarding the majority of currently available literature that reports on revascularisation strategies for PAD is that it does not focus on CLI patients specifically and studies them as a minor part of the complete cohort. Bes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
83
1
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(94 citation statements)
references
References 134 publications
0
83
1
9
Order By: Relevance
“…Since the initial application of plain balloon or percutaneous transluminal angioplasty, several novel endovascular approaches and devices have been released on the market (for example, bare metal stents, cryoplasty, atherectomy devices, stent‐grafts, drug‐eluting stents, and drug‐eluting balloons). In general these devices have been studied in relatively small and selected patient populations, often not including CLI patients 62. The only RCT directly comparing open bypass surgery with endovascular therapy (ie, plain balloon angioplasty) in CLI patients is the BASIL trial, which overall showed no differences between the treatment groups with respect to AFS at 1 and 3 years of follow‐up based on an intention‐to‐treat analysis 4.…”
Section: Revascularization Strategies In CLImentioning
confidence: 99%
See 2 more Smart Citations
“…Since the initial application of plain balloon or percutaneous transluminal angioplasty, several novel endovascular approaches and devices have been released on the market (for example, bare metal stents, cryoplasty, atherectomy devices, stent‐grafts, drug‐eluting stents, and drug‐eluting balloons). In general these devices have been studied in relatively small and selected patient populations, often not including CLI patients 62. The only RCT directly comparing open bypass surgery with endovascular therapy (ie, plain balloon angioplasty) in CLI patients is the BASIL trial, which overall showed no differences between the treatment groups with respect to AFS at 1 and 3 years of follow‐up based on an intention‐to‐treat analysis 4.…”
Section: Revascularization Strategies In CLImentioning
confidence: 99%
“…Patients in the highest risk group have a 1‐year AFS after open bypass surgery of ≈45%, and bypass surgery is therefore not preferred in this high‐risk population. Other studies also identified risk factors for bypass surgery,36 and showed that the conduit used is a major procedural factor influencing prognosis after bypass surgery 62, 78…”
Section: Revascularization Strategies In CLImentioning
confidence: 99%
See 1 more Smart Citation
“…It is also used to treat critical limb ischemia as a last resort with reasonable success. 4,5 Open surgical lumbar sympathectomy has been replaced by an endoscopic retroperitoneal approach. However CT guided lumbar sympathectomy is precise, safe and gives equivalent results without the morbidity associated with surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Šuntavi-mo išeičių metaanalizė parodė, kad naudojant alternatyvias autologines venas pirminis veikimas po 5 metų buvo 46,9 proc., antrinis veikimas -66,5 proc., pėda buvo išsaugota 76,4 proc. atvejų [48].…”
Section: Medikamentinė Terapija Antikoaguliantaiunclassified